Control of charge migration in molecules by ultrashort laser pulses - Golubev, Nikolay V.; Kuleff, Alexander I. (Physical review. A, Atomic, molecular, and optical physics, 2015)
Due to electronic many-body effects, the ionization of a molecule can trigger ultrafast electron dynamics appearing as a migration of the created hole charge throughout the system. Here we propose a scheme to control the charge-migration dynamics with a single ultrashort laser pulse. We demonstrate by fully ab initio calculations on a molecule containing a chromophore and amine moieties that simple pulses can be used to stop the charge-migration oscillations and localize the charge on the desired site of the system. We argue that this control may be used to predetermine the follow-up nuclear rearrangement and thus the molecular reactivity.
Gesehen am 27.07.2020